From Theory to Interpreting the Practice: Exploring the Role-play to Teach DevOps - Mota, Lucas Lima; Santos, Rodrigo Pereira dos; Fontão, Awdren; Araújo, Allysson Allex (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3519, 2024)
[Context] While Role-play (RP) has recently attracted increased attention due its capability as an active learning method in Software Engineering (SE) education, a research gap remains regarding its adoption within the context of DevOps, a critical area in SE. [Objective] This study investigates a RP-based teaching model for DevOps. [Method] We follow an empirical, experimental, and descriptive research approach, employing structured questionnaires and participant observation based on three RP sessions (n=30 students). Data analysis included Descriptive Statistics and Thematic Content Analysis. [Results] In summary, 90% of the students agreed that RP, when compared to an usual DevOps class, was more captivating. Moreover, 93.3% of them agreed that RP contributed to their learning. Pair-based learning and integration of industry tools were highly favored by students according to qualitative results. [Contributions] We offer an RP-based teaching model that encourages collaboration and technical proficiency in SE students. Our proposal can also serve as a potential source of inspiration for companies designing in-company training processes.